Seasonal dynamics and tree foliar habit drive the rhizobacterial diversity in congeneric Ficus species from Northern Western Ghats, India - Salunkhe, Vaishnavi H.; Kunte, Pooja S.; Paul, Dhiraj; Kasodekar, Amol K.; Kadoo, Narendra Y. (Rhizosphere, 2023)
Tree species, annual climatic cycle, and geochemical properties influence the tree rhizospheric microbiome. However, its understanding in the moist deciduous forest of Northern Western Ghats (NWG), India, is limited. Moreover, the effects of foliar habits of trees and seasonal variations on rhizobacterial communities across congeneric tree species are unexplored. Hence, we employed high throughput 16 S rRNA gene sequencing to examine the effects of foliar habits of congeneric tree species and seasonal influences on the rhizobacterial community. For this study, rhizospheric soil from Ficus arnottiana (deciduous) and Ficus talboti (evergreen) trees from NWG, India, was collected during three seasons (summer, monsoon, and winter) and subjected to high throughput sequencing. A total of 3031 amplicon sequence variants (ASV) were observed, of which 1257 and 1181 ASV were unique to F. arnottiana and F. talboti, respectively, and 593 ASV were common to both species. The phyla Actinobacteria, Proteobacteria, Acidobacteria, and Chloroflexi were ubiquitous and contributed >90% to the rhizobacterial community. Some bacterial phyla were exclusively associated with either of the tree species and seasons. Different bacterial phyla performed similar functions in different seasons, indicating their functional redundancy and emphasizing their resilience and adaptability across seasons. It was observed that seasonal dynamics mainly drove the rhizobacterial diversity; however, it was also influenced by the foliar habits of the trees and geochemical properties. The study enhances the understanding of congeneric tree microbiomes and offers valuable insights into their potential applications through microbiome engineering.
Keywords: Amplicon variants; Bacterial diversity; Ficus arnottiana; Ficus talboti; Rhizosphere